INSTITUTIONALIZING CUSTOMARY COURT IN INDONESIAN JUSTICE SYSTEM AS AN EFFORT TO REALIZE ACCESS TO JUSTICE RIGHT FOR INDIGENOUS PEOPLE - Mayastuti, Anti; Trini H, Luthfiyah; Lukitasari, Diana (IJCLS (Indonesian Journal of Criminal Law Studies), 2022)
This study aims to find customary court institution form in an effort to reinstitute customary court in Indonesia. This research is a prescriptive doctrinal legal research, using statutory and conceptual approaches. The data used is secondary data in the form of primary legal materials, while data analysis technique used is qualitative non-positivistic using hermeneutic interpretation method. Customary disputes are included in the realm of material law that occur in the space of indigenous peoples, if they are resolved by a different formal legal institution, namely the general court as regulated in Law no. 21 of 2001 on Special Autonomy for Papua Province. In principle, the customary court is the last judiciary based on customary law, but efforts to obtain justice (access to justice) and the truth are the human rights of everyone. Therefore, everyone who seeks justice must be interpreted as the right to obtain fair recognition, guarantee, protection and legal certainty and be treated equally before the law. The idea of reviving customary justice is important because as a body of customary courts it is in charge of adjudicating customary law disputes that occur in the community.